ANALYSIS OF THE 'URF CONCERNING THE PROHIBITION OF NGALOR NGULON MATRIMONY IN TUMPAKKEPUH VILLAGE, BAKUNG, BLITAR - Rivaniansyah Siacahyo Winarno; Saipul Nasution; Jamhuri; Iman Nur Hidayat; Meitria Cahyani (Universitas Darunnajah Jakarta, Indonesia, 2025)
This study examines the practice of preventing marriage known as